The hunt for ancient Israel: essays in honour of Diana V. Edelman - Shafer-Elliott, Cynthia; Joachimsen, Kristin; Ben Zvi, Ehud; Viviano, Pauline A.; Edelman, Diana Vikander (Equinox, 2022)
"This volume celebrates the contribution of Diana V. Edelman to the field. It includes essays addressing Biblical themes and texts, archaeological fieldwork, historical method, social memory and reception history"--